Effectiveness of Transitional Interventions in Improving Patient Outcomes and Service Use After Discharge From Psychiatric Inpatient Care: A Systematic Review and Meta-Analysis - Hegedüs, Anna; Kozel, Bernd; Richter, Dirk; Behrens, Johann (Frontiers in Psychiatry, 2020)
Background: The transition from psychiatric hospital to community is often hindered by challenges that influence community adjustment and continuity of care. Transitional interventions with bridging components are provided prior to discharge and continue beyond inpatient care. They provide continuity of care and may be effective in preventing readmission. We aimed to assess the effectiveness of transitional interventions with pre- and post-discharge components in reducing readmissions and improving health-related or social outcomes of patients discharged from psychiatric hospitals. Methods: We conducted a systematic review by searching electronic databases (MEDLINE, Embase, Cochrane Library, CINAHL, PsycINFO, and Psyndex) and included randomized, non-randomized, and one-group study designs. A random effects meta-analysis was conducted with randomized controlled trials (RCTs) reporting data on readmission rates. Other study designs were synthesized qualitatively. Results: After screening 2673 publications, 16 studies (10 RCTs, three quasi-experimental, and three cohort studies) were included and nine RCTs were included in the meta-analysis. The tested interventions included components from case management, psychoeducation, cognitive behavioral therapy, and peer support. All studies with significant improvements in at least one outcome provided elements of case management, most frequently in combination with cognitive behavioral therapy and psychoeducation. Readmission rates during follow-up ranged between 13-63% in intervention groups and 19-69% in control groups. Overall, we found an odds ratio of 0.76 (95% confidence interval = 0.55-1.05) for readmission due to transitional interventions. Heterogeneity was low at only 31% (p = 0.17) and the funnel plot indicated no obvious publication biases. Conclusions: We observed that transitional interventions with bridging components were no more effective in reducing readmission than treatment as usual; however, these results are based on limited evidence. Therefore, additional high-quality research is required to conclude the effectiveness of transitional interventions. Nevertheless, transitional interventions with bridging components are preferred by service users and could be an alternative to strategies regularly employed.